Screening and Behavioral Management: Obesity and Weight Management - Nicholson, Robert (2008)
Individuals with migraine headaches who are obese or overweight may be at elevated risk for experiencing more frequent migraines and for developing chronic migraine. This makes it imperative that clinicians consider including weight management as part of a migraine treatment plan in situations where the patient is overweight or obese. Weight loss and weight maintenance therapy should employ a combination of behavioral strategies, in particular nutritional education, dietary intervention, and exercise counseling, as a first line intervention. Weight loss medications are considered a secondary treatment; however, when weight loss medications are used, it is vital to monitor the influence of the medication on headache. Similarly, a clinician considering migraine prophylaxis needs to consider whether the pharmacologic agent being considered influences weight gain or loss.